Dynamical and Static Charge Structure Factors of Doped Zigzag Nanotubes. (15th June 2020) - Rezania, H.; Azizi, F.
Abstract : We present the behaviors of both dynamical and static charge susceptibilities of doped zigzag graphene like nanotube using the Green's function approach in the context of tight binding model Hamiltonian. Specially, the effects of tube diameter, gap parameter and electron doping on the the plasmon modes of zigzag nanotube are investigated via calculating correlation function of charge density operators. Our results show the increase of gap parameter leads to decrease intensity of charge collective mode. Also the frequency position of the collective mode tends to higher frequencies with increase of gap parameter. We also study the effects of chemical potential on frequency positions of plasmon mode of zigzag nanotube. Finally the temperature dependence of static charge structure factor of armchair graphene nanoribbon is studied. The effects of tube diameter and gap parameter on the temperature dependence of static structure factor are addressed in details.